Critical Analysis of Healthcare Delivery Models: Addressing Gaps in Accessibility, Quality, and Efficiency - Al johani, Hind Saad; Alaway, Nahla Abdulrahman; Almushali, Rawan Abduljabar; Mutlaq, Ahmed Abdullah; Fadhul, Esraa Khalid; Shiha, Emad Abdulrahman; Alharbi, Essa Opedallah; AL khaibari, Abdulrahman Mohammed; Alnakli, Hani Moslih; Alahmadi, Manal Masad (Journal of Ecohumanism, 2024)
Healthcare delivery systems have determinative implications for the availability, cost, effectiveness, and patient experiences of society’s medical care system. More recent developments, including value-based care and integrated models, are nevertheless characterized by such disparities, most especially for the rural and economically less privileged citizens, thus underlining the role of drastic change. They suggest that the conventional model, such as fee-for-service and managed care, is not effective enough to transform systematic problems, while new models like patient-centered medical homes and Accountable Care Organizations could develop more effective frameworks. However, these innovations have drawbacks like poor scalability, non-uniform take-updates, and erratic policy intervention, which makes them insufficient to fill the gaps in accessibility and efficiency in one go. The ten barriers discussed here are geographical location, shortage of these specialists, and cost to patients, which imply the need to maintain equity in dispensing healthcare services. Additionally, established indicators of quality demonstrate that there is considerable instability in the results associated with patient satisfaction, clinical results, and organizational effectiveness; this underscores the need for the further application of ICTs such as telehealth, artificial intelligence and analytics to underpin successful processes and support decision-making. This work examines the existing models of the specified problem in detail, categorizes the problem into critical areas of improvement, and synthesizes the problem using literature reviews, quantitative assessment, and presentation of the problem graphically. It is supposed to offer a set of recommendations on how to achieve this goal and incentivizing innovative care networks, building out digital health, and advancing policy changes that support population-health approaches to delivering care. Filling these gaps is crucial for getting a healthcare system that is fair, cheap and capable of producing quality health for all population types as they need.